Linguistic world view in the poetic texts of Lesya Ukrainka’s collection “On the Wings of the Songs” - Danyliuk, Nina (Ukrainian linguistics, 2017)
The article deals with the study of the artistic expressive means of the creation of a linguistic world view in the poetic texts of Lesya Ukrainka’s collection “On the Wings of the Songs” (Lviv, 1893). The materials of the lexicographic work “Dictionary of Lesya Ukrainka’s Language (on the basis of the collection “On the Wings of the Songs”)” in 2 volumes (Lutsk, 2012, 2016) were applied in the study. The nouns used in the microtexts of the dictionary give an opportunity to imagine Lesya Ukrainka’s linguistic world view which was modeled on the basis of key words. Lesya Ukrainka’s linguistic world view is formed by the names of kinship (мати (матінка, матуся), мама, ненька, отець, син (синонько), дочка, дід (дідусь), дитя, дитина (дитинонька), діти (дітки), онуки), plants (верба, дуб, тополя, сосна, калина; барвінок, рожа (роженька), рута, любисток, конвалія, льон), animals and birds (кінь, козеня, корова; голубка, соловейко, чайка), celestial bodies (зоря, зірка (зіронька), місяць, молодик), changes in nature (зима, літо, день, дощ, вітер), geographical objects (балка (балочка), бережок (бережечок), яр (ярочок), гора, круча, бескид; бір, гай, діброва, ліс, луг; річка (річенька, річечка), море), places of living (хата, будинок), utensils (колиска), прикрас (вінок, кораль), traditional ceremonies and their participants (дівич-вечір, молода, староста (старостонька), дружка, кобзар, лірник), abstract notions (бажання, біда, воля, добро, доля, дух, душа, жаль, журба, мрія) and etc. The analyzed fragments of the Ukrainian national linguistic world view reflect the ethnic linguistic thinking of Lesya Ukrainka and prove that she was a Ukrainian. The data gathered in the “Dictionary of Lesya Ukrainka’s Language” compiled on the basis of the collection “On the Wings of the Songs” enable scholars to study an individual linguistic world view. Information about the author:Nina Danyliuk –Dr Hab, Prof. of the Department of the Ukrainian Language, Lesya Ukrainka Eastern European National University (Ukraine).E-mail: danyluk@vnu.edu.ua__________References• Arutjunova N.D. (1999) Jazyk i mir cheloveka [Language and Human World]. Moscow: Jazyki russkoj kul’tury, 896 p. (in Russian).• Yermolenko S.Ya. (ed.) (2001) Ukrainska mova. Korotkyi tlumachnyi slovnyk linhvistychnykh terminiv [Ukrainian Language. A Short Explanatory Dictionary of the Linguistic Terms]. Kyiv: Lybid’, 224 p. (in Ukrainian).• Zhaivoronok V. (2007) Ukrainska etnolinhvistyka [Ukrainian Ethnolinguistics]. Kyiv: Dovira, 262 p. (in Ukrainian).• Serebrjannikov V.A. (ed.) (1998) Rol’ chelovecheskogo faktora v jazyke. Jazyk i kartina mira [The Part of Human being Factor in Language. Language and World Image]. Moscow: Nauka, 212 p. (in Russian).• Sokolovskaja Zh.P. (1999) “Kartina mira”: sistemnost’, modelirovanie i leksicheskaja semantika [“Picture of the world”: the system, modeling and lexical semantics], part 4. Jalta, 173 p. (in Russian).• Fedyk O. (2000) Mova yak dukhovnyi adekvat svitu (diisnosti) [Language as spiritual adekvat of world (reality)]. Lviv: Misioner, 299 p. (in Ukrainian).• Bartmiński J. (2000) Językowe podstawy obrazu świata [Linguistics basis of World Image]. Lublin: Wyd-wo Uniwersytetu Marii Curie-Skłodowskiej, 318 p. (in Polish).
Keywords: linguistic world view, artistic expressive means, key word, epithet, metaphor, symbol, poetic text, “Dictionary of Lesya Ukrainka’s Language (on the basis of the collection “On the Wings of the Songs”)”